2004
DOI: 10.1046/j.1472-765x.2003.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhodovulum sulfidophilum in the treatment and utilization of sardine processing wastewater

Abstract: Aims: Rhodovulum sulfidophilum was grown in settled undiluted and nonsterilized sardine processing wastewater (SPW). The aims were to evaluate the effects of inoculum size and media on the biomass production with simultaneous reduction of chemical oxygen demand (COD). Methods and Results: Three levels of inoculum size (10, 20 and 30% v/v) developed in glutamate-malate media (GMM) or settled and undiluted SPW were compared. The highest biomass (4AE8 g l )1 ) was obtained after 96-h culture with 20% (v/v) inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
1
21
1
1
Order By: Relevance
“…The great amounts of effluents from animal food industries has led to investigations on the use of these by-products as substrates for the growth of phototrophic bacteria that consume organic matter and produce bacterial biomass (PONSANO; LACAVA; AZAD et al, 2004;KANTACHOTE;TORPEE;UMSAKUL, 2005). Due to the nutritional composition of this biomass, some authors have suggested its use as a biofertilizer and animal feed supplement (PONSANO; LACAVA; PONSANO et al, 2004;KANTACHOTE;TORPEE;UMSAKUL, 2005).…”
Section: Production and Drying Of Biomassmentioning
confidence: 99%
“…The great amounts of effluents from animal food industries has led to investigations on the use of these by-products as substrates for the growth of phototrophic bacteria that consume organic matter and produce bacterial biomass (PONSANO; LACAVA; AZAD et al, 2004;KANTACHOTE;TORPEE;UMSAKUL, 2005). Due to the nutritional composition of this biomass, some authors have suggested its use as a biofertilizer and animal feed supplement (PONSANO; LACAVA; PONSANO et al, 2004;KANTACHOTE;TORPEE;UMSAKUL, 2005).…”
Section: Production and Drying Of Biomassmentioning
confidence: 99%
“…Besides that, the availability of organic matter in the substrate and the low concentration of metabolic compounds in the beginning of the growth curve rendered these findings favorable. Some authors found much higher cell mass concentrations when growing phototrophic organisms in industry wastewaters but, in those cases, initial organic matter and inoculum levels were also much higher than the ones used in this study and/or nutritional supplementation was adopted (Prasertsan et al 1997;Azad et al 2001Azad et al , 2003. So, from third day on, cell mass production and COD reduction were less expressive, probably due to decrease of organic substrate and increase of byproducts from bacterial growth.…”
Section: Characteristics Of the Bacterial Growthmentioning
confidence: 63%
“…This happens because the particular characteristics of each industrial effluent derive from crude material composition, water supply essence and reuse and industrial processing techniques (Liu 2007). For settled and unsettled wastewaters from sardine processing industry, for example, pH values from 6.2 to 6.3; 63,000 mg l -1 COD and 10.88 mg l -1 TN were described (Azad et al 2001(Azad et al , 2003. For white fish filleting plants, Arvanitoyannis and Kassaveti (2008) reported the generation of wastewaters with 50 kg Chemical Oxygen Demand (COD) and Prasertsan et al (1993) reported 5.3-8.3 pH; 5,950-157,080 mg l -1 COD; 19.30-82.22 g l -1 TS and 666-32,182 mg l -1 OG for liquid effluents from different seafood processing plants.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the method is characterized by a simple treating process and no excess sludge pollution. Some researchers have proposed to combine wastewater treatment with biomass recovery [18][19][20]. The PSB biomass is rich in single-cell protein, biopolymers, antimicrobial agents, carotene, pantothenic acid, and therapeutic compounds.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%